Radium-Derived Water Mixing and Associated Nutrient in the Northern South China Sea - Liu, Jianan; Du, Jinzhou; Wu, Ying; Liu, Sumei (Frontiers in Marine Science, 2022)
The nutrient plays an important role as biogenic element in modulating marine productivity and water mixing usually facilitates the transportation of nutrient in the coastal ocean. In the present study, the distributions of the naturally occurring radioisotope 226Ra and 228Ra in the surface and water column of the northern South China Sea (NSCS) have been investigated to estimate oceanic mixing and nutrient supplies. We identified three masses of the South China Sea Warm Current (SCSWC), South China Sea Branch of Kuroshio (SCSBK) and shelf water in June 2015 (summer), but only SCSWC and SCSBK were observed in March 2017 (spring). The fraction of the SCSBK in summer was estimated to be an average of 0.25±0.16, which was lower than that in spring of 0.57±0.32 in our study area. The horizontal mixing from the Pearl River plume revealed an eddy diffusion of (1.2±0.79)×105 cm2/s and advection velocity ω of 0.25±0.16 cm/s in the slope region. In the water column, the best-fit exponential curve gradient of 228Ra lead to a vertical diffusion coefficient of 0.43±0.33 cm2/s that down to the subsurface of the upper 1000 m, and an upward vertical diffusion coefficient was revealed as 18±9.9 cm2/s from the near-bottom. Combining the nutrient distributions, horizontal mixing from the Pearl River plume carried (5.6±4.9)×102 mmol N/m2/d, 2.2±2.0 mmol P/m2/d and (4.1±3.9)×102 mmol Si/m2/d in very surface layer, suggesting that shelf water may play a significant role in nutrient sources of the slope of the NSCS during June 2015. The upward vertical mixing supplied 2.7±1.6 mmol N/m2/d, 0.18±0.11 mmol P/m2/d and 15±8.4 mmol Si/m2/d to the upper layer, which appeared to be more important compared to atmospheric deposition, and rivaled submarine groundwater discharge.